Comparative Tandem Mass Tag-Based Quantitative Proteomic Analysis of Tachaea chinensis Isopod During Parasitism - Li, Yingdong; Li, Xin; Han, Zhibin; Xu, Weibin; Li, Xiaodong; Chen, Qijun (Frontiers in Cellular and Infection Microbiology, 2019)
Parasitic isopods perforate and attach to the host integument via the mandibles, then feed on hemolymph and exudate from the wounds. Such isopods attack a variety of commercially important fish and crustacean hosts. Like other hematophagous parasites, isopods employ biomolecules that inhibit host blood conglutination and defense. In the present study, a tandem mass tag-based quantitative proteomic approach was used to identify differentially expressed proteins in Tachaea chinensis parasites of shrimp, by comparing parasitic (fed) and pre-parasitic (unfed) individuals. We identified 888 proteins from 1510 total peptides, with a significant difference in 129 between the fed and unfed groups. Among these, 37 were upregulated and 92 were downregulated in unfed T. chinensis. This indicates that T. chinensis may require more energy before parasitism during its search for a host. In addition, as is the case for other blood-sucking parasites, it might secrete antihemostatic, anti-inflammatory and immunomodulatory molecules to facilitate blood meal acquisition. Our study is the first to use a TMT-based proteomic approach to analyze the proteome of isopod parasites, and our results will facilitate our understanding of the molecular mechanisms of isopod parasitism on crustaceans.